1987
DOI: 10.1063/1.98357
|View full text |Cite
|
Sign up to set email alerts
|

Optical time-of-flight measurement of carrier diffusion and trapping in an InGaAs/InP heterostructure

Abstract: We have measured the diffusion and trapping of photoexcited hot carriers in an InGaAs/InP heterostructure using an optical time-of-fight technique with picosecond time resolution. The ambipolar diffusivity is found to decrease by an order of magnitude between 4 K and room temperature, and the efficiency of trapping of carriers into the well increases rapidly in the same temperature range. A mean trapping time of 4 ps is measured for a 50 Å well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Most of the carriers recombining in the wells come from the barriers. At low temperatures, the carrier collection efficiency is relatively high as evidenced by the absence of the PL emissions from the barrier layers, and large portion of the carriers generated in the barrier layers transfer to the wells since the carrier transfer time is very short compared to the recombination time, either radiative or nonradiative, in the barrier layers [10][11][12][13]. Therefore the PL intensities of the three samples are very comparable as shown in Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Most of the carriers recombining in the wells come from the barriers. At low temperatures, the carrier collection efficiency is relatively high as evidenced by the absence of the PL emissions from the barrier layers, and large portion of the carriers generated in the barrier layers transfer to the wells since the carrier transfer time is very short compared to the recombination time, either radiative or nonradiative, in the barrier layers [10][11][12][13]. Therefore the PL intensities of the three samples are very comparable as shown in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…obel et al [10] also observed this phenomenon, and they attributed it to the difference in initial excess energy of photo-excited carriers between the two samples. The carrier capture is a process of relaxation of carriers from higher energy to lower energy by carrier scattering, i.e., interaction of carriers with phonons [13]. The time-resolved PL results suggest that the larger the energy difference between the initial and final states, more steps of scattering will be needed for carrier to lose its energy by emission of phonons, and the slower the trapping process.…”
Section: Article In Pressmentioning
confidence: 97%
“…For the InP reference sample, these excited carriers diffused into MQWs and enhanced radiative recombination, as well as PL intensity. However, for the InP-on-Si substrate, due to smaller band gap of the three strained InGaAs interlayers (∼0.76 eV), excited carriers generating from the InP buffer would be easily trapped by these InGaAs "wells" [23], preventing contribution of substrate to the PL intensity of MQWs. Besides, these "wells" could have a strong absorption of light scattering from the MQWs, which would also decrease the PL intensity.…”
Section: Characterization and Discussionmentioning
confidence: 99%
“…In the limit of course the structure will become three-dimensional so there will exist some optimal thickness of the barriers for which carrier tunnelling is sufficiently strong and yet the advantages of two-dimensional confinement are not lost. Measurements of the capture efficiency into a 504 well have been performed by our collaborators at Oxford University (17]. The nature of these experiments has already been described in section barrier thicknesses In the region of 25-30A will be required to promote the necessary heavy hole transfer.…”
Section: Carrier Capture and Equilibriationmentioning
confidence: 99%